An assessment of introducers used for airway management. (3rd December 2021) - Price, L.; Carter, P.; Hodzovic, I.; Alderman, M.; Hughes, G.; Phillips, P.; Varadarajan, V.; Wilkes, A.
Summary: Different introducers are available to assist with tracheal intubation. Subtle differences in the design of introducers can have a marked effect on safety and performance. The Difficult Airway Society's Airway Device Evaluation Project Team proposal states that devices should only be purchased for which there is at least a case–control study on patients assessing airway devices. However, resources are not currently available to carry out a case–control study on all introducers available on the market. This study comprised a laboratory and manikin‐based investigation to identify introducers that could be suitable for clinical investigation. We included six different introducers in laboratory‐based assessments (design characteristics) and manikin‐based assessments involving the participation of 30 anaesthetists. Each anaesthetist attempted placement in the manikin's trachea with each of the six introducers in a random order. Outcomes included first‐time insertion success rate; insertion success rate; number of attempts; time to placement; and distance placed. Each anaesthetist also completed a questionnaire. First‐time insertion success rate depended significantly on the introducer used (p = 0.0016) and varied from 47% (Armstrong and P3) to 77% (Intersurgical and Frova). Median time to placement (including oesophageal placement) varied from 10 s (Eschmann and Frova) to 20 s (P3) (p = 0.0025). Median time to successful placement in the trachea varied from 9 s (Frova) to 22 s (Armstrong) (p = 0.037). We found that the Armstrong and P3 devices were not as acceptable as other introducers and, without significant improvements to their design and characteristics, the use of these devices in studies on patients is questionable. The study protocol is suitable for differentiating between different introducers and could be used as a basis for assessing other types of devices.